Defeating Mooren Ulcer: Timely Diagnosis and Strategic Interventions for Swift Recovery - Priscilia, Florentina; Paramitha, Dewa Ayu Anggi; Aziza, Yulia (Majalah Oftalmologi Indonesia, 2026)
Introduction: Mooren ulcer is a unique and rare manifestation of peripheral ulcerative keratitis of idiopathic origin, triggered by immunological abnormalities, genetic predispositions, and environmental factors. Case Report: We report the successful treatment of a rare case involving a 43-year-old man who presented with a significant worsening of white tissue covering cornea, severe pain, redness, and blurred vision in the left eye. An examination revealed a peripheral ulcer extending centrally with scleral sparing. Ancillary examinations yielded unremarkable findings. The patient was diagnosed with Mooren ulcer and initially treated with topical steroid, which showed no improvement. Therefore, a simultaneous conjunctival resection combined with immunosuppressive therapy was performed. At 1-year follow-up, no pain was reported, vision improved (6/21 to 6/12), and resolved ocular surface inflammation. Discussion: Mooren ulcer is often prone to misdiagnosis due to clinical signs that resemble other differential diagnoses. A meticulous examination is essential to carefully exclude autoimmune and corneal infection. The treatment goals are to arrest the destructive process and facilitate re-epithelization. A stepwise aggressive approach is crucial, starting with topical steroids to control inflammation. However, this single treatment modality may not prevent rapid progression, making conjunctival resection imperative to eliminate the source of collagenase production by cutting off the perilimbal blood vessels’ access to ulcer cites. Combining this with an immunosuppressant effectively maintains a stable condition. Conclusion: This case underscores the importance of timely diagnosis and aggressive treatment in preventing the swift progression of Mooren ulcer.